Catheter-directed thrombolysis for double inferior vena cava with deep venous thrombosis: A case report and literature review. (August 2014) - Wang, Xiaodong; Chen, Zhengxin; Cai, Qianrong
Double inferior vena cava (DIVC) with deep venous thrombosis (DVT) is rare, and there is only one reported case of DIVC with DVT treated by catheter-directed thrombolysis. We report a case of a 32-year-old man with an extensive venous clot involving the infrarenal segment of a double IVC who received filter implantation and catheter-directed thrombolysis.